2012
DOI: 10.1152/ajpendo.00182.2012
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 13 wk of liraglutide treatment on endocrine and exocrine pancreas in male and female ZDF rats: a quantitative and qualitative analysis revealing no evidence of drug-induced pancreatitis

Abstract: A possible association between glucagon-like peptide-1 (GLP-1) analogs and incidences of pancreatitis has been suggested based on clinical studies. In male and female diabetic Zucker diabetic fatty (ZDF) rats, we investigated the effects of continuous administration of liraglutide and exenatide on biochemical [lipase, pancreatic amylase (P-amylase)] and histopathological markers of pancreatitis. Male and female ZDF rats were dosed for 13 wk with liraglutide (0.4 or 1.0 mg·kg(-1)·day(-1) sc once daily) or exena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
79
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 40 publications
13
79
0
2
Order By: Relevance
“…In contrast, hundreds of other studies have investigated effects of these drugs on the pancreas but have not reported adverse effects; a few are referenced here for liraglutide (37)(38)(39). A study, Animals examined 3 3 3 3 3 3 3 3 Endocrine pancreas No abnormality detected 3 3 3 3 3 3 3 3 Exocrine pancreas No abnormality detected 3 3 3 3 3 3 3 3 13-week liraglutide dose levels (mg/kg/day) 0 0.05 0. performed after others had reported potential adverse findings, confirmed the absence of pathology in diabetic rats and also did not show any regional differences in the pancreas induced by liraglutide when the pancreas was divided into four regions and examined by stereology (40). A recent publication used a human islet amyloid polypeptide transgenic model similar to one of the earlier studies, just in mice instead of in rats, treats the animals for 1 year instead of 12 weeks, used 20-25 animals in each group instead of 8, and found no pancreas pathology associated with sitagliptin (25,41).…”
Section: Discussionsupporting
confidence: 57%
“…In contrast, hundreds of other studies have investigated effects of these drugs on the pancreas but have not reported adverse effects; a few are referenced here for liraglutide (37)(38)(39). A study, Animals examined 3 3 3 3 3 3 3 3 Endocrine pancreas No abnormality detected 3 3 3 3 3 3 3 3 Exocrine pancreas No abnormality detected 3 3 3 3 3 3 3 3 13-week liraglutide dose levels (mg/kg/day) 0 0.05 0. performed after others had reported potential adverse findings, confirmed the absence of pathology in diabetic rats and also did not show any regional differences in the pancreas induced by liraglutide when the pancreas was divided into four regions and examined by stereology (40). A recent publication used a human islet amyloid polypeptide transgenic model similar to one of the earlier studies, just in mice instead of in rats, treats the animals for 1 year instead of 12 weeks, used 20-25 animals in each group instead of 8, and found no pancreas pathology associated with sitagliptin (25,41).…”
Section: Discussionsupporting
confidence: 57%
“…We did not observe increases in pancreatic amylase gene expression, and lipase mRNA transcripts were significantly lower after Ex-4 administration. Furthermore, studies of pancreatic enzyme levels in rodents have been inconsistent, demonstrating either no change or small increases in amylase following administration of GLP-1R agonists (17,(33)(34)(35). Our current studies demonstrate that serum lipase levels were lower, whereas amylase levels and pancreatic content of amylase and lipase proteins (Supplementary Table 2) remained similar after treatment with Ex-4.…”
Section: Discussionmentioning
confidence: 44%
“…There was a nonsignificant difference in duct cell proliferation after 6 weeks of treatment. These observations and the findings of other studies [27][28][29][30][31][32] raise the issue of whether GLP-1-based therapies are a potential risk for pancreatitis; some studies did not observe this effect [33,34], however, which may reflect the animal model used, the age of the animals and/or the labelling and counting methods used for proliferating cells. In our study, there was no indication of a systemic inflammatory state.…”
Section: Discussionmentioning
confidence: 88%